8+19n-3=7n+89-2n

Simple and best practice solution for 8+19n-3=7n+89-2n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+19n-3=7n+89-2n equation:


Simplifying
8 + 19n + -3 = 7n + 89 + -2n

Reorder the terms:
8 + -3 + 19n = 7n + 89 + -2n

Combine like terms: 8 + -3 = 5
5 + 19n = 7n + 89 + -2n

Reorder the terms:
5 + 19n = 89 + 7n + -2n

Combine like terms: 7n + -2n = 5n
5 + 19n = 89 + 5n

Solving
5 + 19n = 89 + 5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-5n' to each side of the equation.
5 + 19n + -5n = 89 + 5n + -5n

Combine like terms: 19n + -5n = 14n
5 + 14n = 89 + 5n + -5n

Combine like terms: 5n + -5n = 0
5 + 14n = 89 + 0
5 + 14n = 89

Add '-5' to each side of the equation.
5 + -5 + 14n = 89 + -5

Combine like terms: 5 + -5 = 0
0 + 14n = 89 + -5
14n = 89 + -5

Combine like terms: 89 + -5 = 84
14n = 84

Divide each side by '14'.
n = 6

Simplifying
n = 6

See similar equations:

| 2(3x-4)=5(8-2x) | | 7(2x-1)=3(15-4x) | | 6x^2+18=-21x | | -2v^2-5v-3=0 | | 1000=x+(x*.8)+(x*.3) | | 3.5q-1.4-5.9q=-3.4q-4.4 | | 1000=x+(x*.8)+(x*.5) | | -5y+4=-6y+5 | | 3x^2-14x=-18 | | 12x+6-3=11x-3 | | -10+3+6=-10 | | -4v^2-13v-3=0 | | -(8y+3)-(-7-4)=-1 | | 0.30(18)+0.05x=0.15(18+x) | | 8-4x+-6x=50 | | 4(2x-1)=2(3x+8) | | 4(3x+12)=2(2x+4) | | 1000=x+(x*.8) | | 3=2e^4x | | 9(x-36)=18 | | 2(x+4)=6(2x+3) | | 7(4x+6)+15= | | 4x-5=11-89 | | 6x+35=15x-55 | | 5a-3-4a+3=8 | | (4x^2+3x+5)-(6x^2-8)= | | 6a-2-5a+2=-2 | | X^2+17x=-72 | | -4a+3a-6=-4 | | 9x-19=5x+12 | | 6q-9=4q-19 | | c-5*4=-48 |

Equations solver categories